Social enterprise sustainability : an exploratory case of selected private islamic schools in Malaysia - Mohd Ali Bahari bin Abdul Kadir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
This research explores the issue pertaining to what social enterprise is. It specifically focuses on the notion of social enterprise sustainability and the factors that contribute to social enterprise sustainability. The main purpose was to acquire comprehensive understanding of how social enterprises are sustained as well as to investigate the factors that contribute to their sustenance from the context of private Islamic schools in Malaysia. This research reviewed three relevant literature streams; the business entrepreneurship, social entrepreneurship and Islamic education literature to conceptualize the elements of social enterprise sustainability and contextualized it with regards to private Islamic schools in Malaysia. The literature indicated that the discussion pertaining to sustainability in social enterprise is fragmented, underdeveloped and lacking of empirical evidence. Therefore, these gaps provide strong ground for this study which employed a qualitative methodology. A multiple-case study research design was used to discover the intricate details about this central phenomenon in order to gain beneficial insights about it. This method allowed the researcher to retain the holistic and meaningful characteristics of real life events – such as individual life cycles, small group behaviour, organizational and managerial process, neighbourhood change and school performance. Nine owners and/or founders representing nine private Islamic schools were chosen to participate in the study. They were interviewed in-depth and observed on multiple occasions. Documents related to their schools were gathered and photos of their schools and activities were taken as evidences. The data from these multiple sources of evidences were initially analyzed case by case and later across cases. Analysis based on the results from the individual case resulted in several themes and sub-themes that were also present across the nine cases. Those themes and sub-themes represent five interrelated sustainability factors namely financial, physical facilities, human, altruism and school system. In summary, the study found that for social enterprises to sustain, they must seek ways to have pertinent sources of fund, prudently acquire and develop their physical facilities, wisely retain the workforce, rightly nurture the culture of altruism and finally deliver the products and/or services to the patrons in a systematic manner. This model of social enterprise sustainability developed in the study might be beneficial not only to social entrepreneurs (e.g. owners of private Islamic schools) but also policy makers involved in the development of relevant guidelines as well as academics responsible to further enhance the research in the field of social enterprise. Therefore, this study definitely provides new knowledge and important insights with regards to the issue of social enterprise which gradually being acknowledged in Malaysia.